2008
DOI: 10.1021/es800518g
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Air−Water and Surface−Deep Water Gradients of PCBs Using Polyethylene Passive Samplers

Abstract: Polyethylene passive samplers (PEs) were deployed in a vertical array (bottom water, surface water, near-surface air) to study the cycling of active polychlorinated biphenyls (PCBs) between reservoirs in an urban estuary (Narragansett Bay, RI), from May to November 2006. Performance reference compounds were used to account for nonequilibrium of PCBs in PEs. Activity gradients were established from direct comparisons of temperature, salt, and nonequilibrium corrected PE concentrations. The uncertainty of determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(82 citation statements)
references
References 28 publications
2
80
0
Order By: Relevance
“…Among these transport pathways, only molecular diffusion mainly involves the freely dissolved chemicals and is a direct reflection of the chemical fugacity difference between the two phases. 7,8 In this regard, the direction and magnitude of diffusion fluxes across the sediment−water interface are vital parameters for discerning whether a sediment acts as a source or sink of chemicals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among these transport pathways, only molecular diffusion mainly involves the freely dissolved chemicals and is a direct reflection of the chemical fugacity difference between the two phases. 7,8 In this regard, the direction and magnitude of diffusion fluxes across the sediment−water interface are vital parameters for discerning whether a sediment acts as a source or sink of chemicals.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This may be why Morgan et al [8] did not detect higher than normal concentrations of PCBs in bottom water after two spring-tide events, which presumably would have caused the release of large amounts of PCBs from sediment to overlying water.…”
Section: Hydrodynamicsmentioning
confidence: 95%
“…Morgan et al [8] observed a higher concentration ratio for PCBs between bottom and surface water of Narragansett Bay in July and August, while the gradient gradually decreased or even reversed after August, suggesting more outflows of PCBs from sediment in the warmer season. Also, diffusion coefficients that may depend on temperature can be corrected by…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations